Задание граничных условий теплообмена в зоне поршневых колец поршня транспортного дизеля на начальных стадиях проектирования - Пылев, Владимир Александрович; Нестеренко, Ирина Александровна (НТУ "ХПИ", 2017)
Проанализированы способы задания граничных условий и законов управляющих функций для поршней транспортного дизеля. Предложены варианты упрощенного задания граничных условий и законов управляющих функций с целью сокращения времени для расчета переходных процессов нагружения двигателя на начальных стадиях проектирования поршня. Произведена оценка влияния предложенных вариантов задания граничных условий и законов управляющих функций на температурное и термонапряженное состояние кромки камеры сгорания поршня.

We have been analyzed methods for defining boundary conditions of and the laws of the control functions for vehicle diesel engine pistons. Also we have been proposed simplified versions of defining boundary conditions of and the laws of the control functions in order to reduce the time to calculate the engine load transient processes in the early stages of design of the piston. The result was evaluated the influence of the proposed options for setting boundary conditions and the laws of the control functions in the transition processes on the temperature and thermo-stressed state of the piston combustion chamber edge.
Setting the heat transfer boundary conditions in the area of piston rings piston diesel vehicle in the initial stages of design
Keywords: камера сгорания; управляющие функции; переходной процесс; коэффициент теплоотдачи; piston; combustion chamber; boundary conditions; control functions; transition process; diesel engine